I have two urns, each containing $N$ marbles. Urn $A$ has $K_A$ blue marbles and the rest are red, while Urn $B$ has $K_B$ blue marbles and the remaining marbles are red.
I then sample pairs of marbles, one from each urn, without replacement. If I repeat this $k \leq N$ times, on average how many pairs of marbles will have mismatched colours? What is the variance of this random variable?
My first attempt
Let $X$ be the random variable denoting the number of pairs of marbles with mismatched marbles. $$E[X] = \sum_{i=1}^{k}i\cdot P(X=i)$$ where $$P(X=i) = \frac{\# \text{ microstates with exactly $i$ mismatches}}{\# \text{ all possible microstates}}\,.$$ For the denominator, we may enumerate all possible combinations as in the hypergeometric distribution and use Vandermonde's identity to simplify: $$ \sum_{l} \ {K_A \choose l}{N-K_A \choose k-l}\sum_{m} {K_B \choose m}{N-K_B \choose k-m} = {N \choose k}^2\,.$$
Though it remains to find a similar combinatoric expression for the numerator...
My second attempt
Let $I_i$ be an indicator variable denoting occurrence of a mismatch in the $i^{th}$ pair of marbles. Note that $X = \sum_{i=1}^{k} I_i$. Invoking linearity of expectation: $$ E[X] = E[\sum_{i=1}^{k} I_i] = \sum_{i=1}^{k} E[I_i] $$ Since $E[I_i] = P(I_i = 1)$,
$$ \begin{align} E[X] &= \sum_{i=1}^{k} P(I_i = 1) = \sum_{i=1}^{k}\sum_{\mathbf{I} \in \{0,1\}^{i-1}} P(I_i = 1\;|\;\mathbf{I}) \\ &= \sum_{i=1}^{k}\sum_{\mathbf{I} \in \{0,1\}^{i-1}} P(I_i = 1\;|\;I_{i-1} \land I_{i-2} \dots \land I_{1})P(I_{i-1} \;|\;I_{i-2} \land I_{i-3} \dots \land I_{1})\cdots P(I_1 ) \end{align}$$
This method requires calculating exponentially many conditional probabilities unless there is some recursive relationship (which I'm struggling to derive):
$$ \begin{align}P(I_1 = 1) &= \frac{K_A}{N}(1-\frac{K_B}{N}) + \frac{K_B}{N}(1-\frac{K_A}{N}) = \frac{K_A}{N}+\frac{K_B}{N}-2\frac{K_A}{N}\frac{K_B}{N}\\ \\ P(I_1 = 0) &= 1 - P(I_1 = 1)\\ \\ P(I_2 = 1\;|\;I_1 = 0) &=\;?\end{align}$$
CORRECTION
It seems that $$E[X] = \sum_{i=1}^{k} E[I_i] = k\cdot E[I_1] = k\cdot P(I_1 = 1)$$ But it is not clear to me why it can be argued from symmetry that $E[I_i] = E[I_1]$?